Does Better Business Regulatory Environment Translate to Increased Foreign Direct Investment Inflows? Evidence from Eastern Africa - Bosire, Eric Mokwaro (International Journal of Economics and Financial Issues, 2019)
The private sector plays a pivotal role in social economic development. A thriving business environment creates employment and generates returns that can be re-invested both domestically and internationally. Unfortunately, there has been scanty scholarly exploration on how improvements in doing business environment affect foreign direct investments. For that reason, this paper intended to establish how improvements in doing business environment affect the flow of foreign direct investments into the eastern Africa region. The study used panel data, maintained by the World Bank from 12 eastern Africa countries for the period 2004 through 2017. The World Bank has profiled 11 parameters to define doing business environment, namely; doing business, starting a business, dealing with construction permits, getting electricity, registering property and getting credit. Others include, protecting minority investors, paying taxes, trading across borders, enforcing contracts and resolving insolvency. GDP per capita, trade openness and Labour Force controlled the relationship between ease of doing business and FDI. Using OLS regression on Pooled data, the paper established a significant influence of ease of doing business variables on FDI. Therefore, the paper concluded that FDI follows the size and quality of the market and production efficiency. Then, the paper advises governments to enact adequate regulations that support the development of the private sector. Keywords: Foreign Direct Investments, Ease of Doing Business, Starting a Business JEL Classifications: C33, F21, F23, O11 DOI: https://doi.org/10.32479/ijefi.8153